Música, Paisagem Sonora e Recurso Social: estudo antropológico do grupo de música popular portuguesa «Cantares da Serra» de Mação (Portugal central) - Jácome, Graziela Armelao (Trabalhos de Antropologia e Etnologia, 2020)
Music, Soundscape and Social Resource: a study of the popular music group Cantares da Serra of Mação (Central Portugal) approaches relevant concepts in the study of musicology trying to understand what music is. For such, we discuss themes like the neologism of Murray Schafer, soundscape, understanding the surroundings acoustically modified in the village of the musical group. Furthermore we raise the discussion of the thematic implicated in the comprehension of Antony Seeger concept, the social resource, understanding its occurrence. The research focuses a non-professional group of popular music formed by 16 women, the majority old. They sing in unison and use varied percussion instruments. They are located in a desertified rural village, like many other in the interior of Portugal. These women are shepherdesses or farmers and made of music an important resource for a healthy maintenance of their life, transforming, at the same time, the sonorities and the social life of the village. They are taught trough musical conservation by memorization, privileging the audition/repetition, repopulating the rural life with their songs, rehearsals and performances.